Yoreme — Ten, který respektuje tradice - Alena Prokopius (Svět Literatury)
The deer dance (Danza del Venado) is a central ritual of the Yaqui tribe inhabiting parts of Mexico and the USA. Dating back to pre-Columbian times, this dance symbolizes man’s connection with nature, represented here by a dancer in the form of a deer. The choreography of the dance, the sounds and the costumes refer to the life and hunting of this animal. Despite the geopolitical divide, the Yaqui retain strong cultural ties, particularly during the annual Easter (Pascoa) celebrations. A key moment in these celebrations is the presentation of the deer dance. Originally purely ceremonial, this ritual has gradually been integrated into Mexican folklore and has become an important representative of the State of Sonora within the Baile Folklórico dance system. Along with other dances, it is now seen as a part of Mexico’s living cultural heritage. However, its inclusion in the Baile Folklórico system raises questions about the authenticity of the representation of Yaqui customs. This paper will focus on the historical development of the deer dance and its current role within the Yaqui community and broader Mexican society.